A Case of STEMI Masquerading Brugada Syndrome: Emphasizing the Importance of Clinical Decision Making in Emergencies - Nirmal Guragai MD; Rahul Vasudev MD; Dhaval Shah MD; Balraj Singh MD; Parminder Kaur MD; Ashen Fernando MD; Fayez Shamoon MD; Raja Pullatt MD; Meherwan Joshi MD; Preet Randhawa MD (SAGE Publishing, 2021)
Brugada syndrome is a rare arrhythmogenic syndrome that is associated with an increased risk of ventricular fibrillation and sudden cardiac death. Electrocardiographic findings include patterns similar to a right bundle branch block (RBBB) and persistent ST-segment elevation in precordial leads (V1 and V2). There are numerous reports of Brugada syndrome mimicking ST-segment elevation myocardial infraction (STEMI); however, we describe a case of 47-year-old male who presented with STEMI mimics Brugada syndrome with preexisting RBBB. The patient developed polymorphic ventricular tachycardia generating into ventricular fibrillation right before catheterization making the diagnosis more challenging. The patient, eventually, was found to have obstructive coronary artery disease and no evidence of abnormal sodium channelopathy on further testing. This case highlights the importance of meticulous history taking and appropriate diagnostic test in establishing proper diagnosis of STEMI in a patient with preexisting RBBB, which can mimic Brugada syndrome.